103 Exploratory segregation of patients upon their levels of anti- mitochondrial antibodies (AMAs) reveals associations between AMAs and disease manifestations. (14th December 2022) - Becker, Yann LC; Boilard, Éric; Rollet-Labelle, Emmanuelle; Lood, Christian; Julien, Anne-Sophie; Leclerc, Joannie; Lévesque, Tania; Urowitz, Murray; Hanly, John; Gordon, Caroline; Bae, Sang-Cheol; Romero-Diaz, Juanita; et al.
Abstract : Background: Mitochondria are intracellular organelles derived from the endosymbiosis between an α-proteobacterium and a primitive eukaryotic cell. Mitochondria thus display pro-inflammatory and antigenic properties, when released into the extracellular milieu. Several cross-sectional studies reported increased levels of anti-mitochondrial antibodies (AMAs) in patients with systemic lupus erythematosus (SLE) and the antiphospholipid syndrome (APS). These autoantibodies also displayed correlations with the SLE disease activity index 2000 (SLEDAI-2K) and associations with various clinical manifestations (e.g. lupus nephritis, thromboses, carotid plaque). In the present study, we aim to detect AMAs against either whole organelles (AwMA), mitochondrial DNA (mtDNA) or RNA (mtRNA) through time in samples from patients included in the SLICC cohort. Methods: Clinically relevant variables (e.g., sociodemographic variables, disease-specific outcomes including death and arterial vascular events (AVE)) were documented and biosamples were harvested upon patient enrolment in the SLICC cohort, as well as at each follow-up visit. AMA levels were measured by in-house direct ELISAs whereas SLE autoantibodies were detected by clinical laboratories. Healthy individuals, defined as having no known illnesses and infectious symptoms at the time of the blood draw, were recruited. 90% confidence intervals were calculated for both limits of the 95% nonparametric two-sided reference intervals for values measured in healthy donors. AMA values were segregated into 3 categories: Normal values were determined as within the inner limits of the range while values outside this range were characterized as abnormal, either lower or higher than the reference interval. (figure 1). Marginal Cox models with AMAs in 3 categories were adjusted for covariables and are presented as [hazard ratio (95% CI)]. Interactions with sex were tested in models with the AMAs as continuous variables. Results: Sera from healthy individuals (n=126) or SLE patients included in the SLICC cohort, from their inclusion, up to 7 years of follow-up (n=1114 patients at baseline, 3577 samples in total). AwMA displayed lower correlations with antibodies to mitochondrial nucleic acids (versus AmtDNA: rs =0.37, and vs AmtRNA: rs =0.38), while antibodies to mitochondrial DNA or RNA shown higher correlations (rs =0.59). During our preliminary analyses on the distribution of the variables, We made intriguing observations regarding patients with AMA levels that were either lower or higher than those of healthy individuals. This information led us to categorize SLE patients as described in the methods and in figure 1. For each of the three antibodies assessed, SLE patients displayed more abnormal AMA levels at baseline than controls. The percentage of patients with higher levels of AwMA and AmtRNA increased at subsequent follow-up visits, while a slight decrease was observed for AmtDNA (figure 2). SLE patients with higher levels of AwMA showed higher risks of death [2.12 (1.18-3.83)]. It is of interest that an inverse relationship was found between AmtRNA and AVEs, with a small subset of patients with low levels of AmtRNA (n = 4), this autoantibody was associated with increased risks of this manifestation [4.46 (1.71-11.66)]. Additionally, patients with higher levels of AmtDNA and AmtRNA displayed increased risks of lupus nephritis [respectively: 3.05(2.05-4.54), and 1.56(1.12-2.18)]. Interestingly, there was an interaction with sex for AmtRNA levels effect on AVEs [males: 0.32 (0.11-0.99). Females: 1.56 (1.11-2.19)], and AmtDNA association with nephritis was only significant in female patients [4.00 (2.51-6.36)] (table 1). Conclusion: These results show that AMAs display different associations with disease manifestations in various clusters of patients. These results prompt for further analyses by machine-learning in order to delineate clusters of clinical interests by adding AMAs in the routine serological assessment of SLE autoantibodies. Acknowledgements: We acknowledge the contribution of the study participants, individual center support staff as well as investigators of the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort project who for the past 20 years have made this study possible. LAY ABSTRACT: The mitochondrion is a part of the cell that controls various biological mechanisms (e.g., energy supply, whether the cell should live or die, control, or produce various cellular components). They are derived, through evolution, from a microbe. Mitochondria may sometimes be jettisoned out of their host cell and subsequently elicit immune reactions – including the production of antibodies. Previous studies indicated that patients with autoimmune conditions such as systemic lupus erythematosus (SLE) and the antiphospholipid syndrome (APS) have antibodies against mitochondria in their blood stream. Presence of these antibodies was associated with increased disease activity and clinical manifestations of these diseases (e.g. kidney disease, arterial vessel disease). In this study, we studied blood samples harvested by an international group dedicated to the study of SLE [i.e., the SLE International Collaborating Clinics (SLICC) cohort] and observed that patients may be clustered into groups, upon their levels of antibodies and/or sex, allowing to have a better appreciation of their risks of death, vascular events, and kidney disease. These results might lead to improved diagnosis and/or prognosis in SLE and thus, in improved care and quality of life for the people living with lupus.